Two years recurrence rate of ovarian and endometrial malignancies following Surgical versus clinical staging - Shokhan Faeq Rashid; Maryam Bakir Mahmood; Taher Abdullah Hussein Hawramy (Advanced Medical Journal)
Background and objectives: Gynecological cancers represent a big burden on national health institutes. Recurrences of these cancers are documented frequently that needed more efforts to prevent or reduce them.  The aim of the study was to know the difference between Standard Surgical Staging and Non-Standard Surgical Staging in gynecological cancers in terms of recurrence rate.